Desempeño laboral y gestión del talento humano en el emprendimiento comunitario Kintia Panki, de la parroquia asunción, cantón Sucúa - Verónica Fernanda, Gavidia Haro (2021)
ABSTRACT: This research refers to the issue of job performance and the management of human talent in community entrepreneurship Kintia Pintia Panki, from Asunción Parish, Sucúa Canton, the relationship between the two proposed variables was analyzed. Chapter I: The problem situation was exposed; most importantly, the lack of technical knowledge on human talent management. The objectives of the investigation were developed, the same that defined the path of the study. Chapter II: The research background was developed, the set of previous works carried out by other authors on the subject of study. Graduate works, postgraduate thesis, articles were used. Chapter III: The methodology and design to be carried out in this research were defined. Being descriptive, explanatory, and correlational, with a non-experimental design Chapter IV: The statistical analysis of the surveys, closed questions, general and specific hypothesis testing, conclusions, and research recommendations were carried out. Chapter V: The research proposal is to provide a manual of functions based on the company's current needs.